Variability in statin-induced changes in gene expression profiles of pancreatic cancer - Gbelcová, Helena; Rimpelová, Silvie; Ruml, Tomáš; Fenclová, Marie; Kosek, Vítek; Hajšlová, Jana; Strnad, Hynek; Kolář, Michal; Vítek, Libor (Scientific reports, 2017)
Statins, besides being powerful cholesterol-lowering drugs, also exert potent anti-proliferative activities. However, their anti-cancer efficacy differs among the individual statins. Thus, the aim of this study was to identify the biological pathways affected by individual statins in an in vitro model of human pancreatic cancer. The study was performed on a human pancreatic cancer cell line MiaPaCa-2, exposed to all commercially available statins (12 μM, 24 h exposure). DNA microarray analysis was used to determine changes in the gene expression of treated cells. Intracellular concentrations of individual statins were measured by UPLC (ultra performance liquid chromatography)-HRMS (high resolution mass spectrometer). Large differences in the gene transcription profiles of pancreatic cancer cells exposed to various statins were observed; cerivastatin, pitavastatin, and simvastatin being the most efficient modulators of expression of genes involved namely in the mevalonate pathway, cell cycle regulation, DNA replication, apoptosis and cytoskeleton signaling. Marked differences in the intracellular concentrations of individual statins in pancreatic cancer cells were found (>11 times lower concentration of rosuvastatin compared to lovastatin), which may contribute to inter-individual variability in their anti-cancer effects. In conclusion, individual statins exert different gene expression modulating effects in treated pancreatic cancer cells. These effects may be partially caused by large differences in their bioavailability. We report large differences in gene transcription profiles of pancreatic cancer cells exposed to various statins. These data correlate to some extent with the intracellular concentrations of statins, and may explain the inter-individual variability in the anti-cancer effects of statins.
Keywords: sekvenční analýza hybridizací s uspořádaným souborem oligonukleotidů; Hydroxymethylglutaryl-CoA Reductase Inhibitors; nádorové buněčné linie; Transcriptome; statiny; Cell Line, Tumor; regulace genové exprese u nádorů; nádory slinivky břišní; Gene Expression Profiling; Humans; Gene Expression Regulation, Neoplastic; lidé; Pancreatic Neoplasms; Oligonucleotide Array Sequence Analysis; stanovení celkové genové exprese; transkriptom